(untitled) (Modern education and development, 2025)
This article explores proverbs and sayings as a significant and autonomous subsystem within phraseology. It analyzes their linguistic features, cultural functions, and structural peculiarities. The study also highlights the importance of proverbs and sayings in language education, intercultural communication, and cognitive linguistics. Special attention is paid to their stability, figurative meaning, and role in expressing collective wisdom